Mytech & Assembly Sdn. Bhd. / Nurul Suhaina Md Nazri - Md Nazri, Nurul Suhaina (Faculty Of Chemical Engineering, 2022)
Industrial training course with code CHE353 is the required course for students to complete their diploma. Students need to undergo industrial training for 4 months which is consist of 17 weeks. Industrial training start on 22 May 2021 until - July 2021. This subject is an important subject as this subject give chances to student in exposed to the working environment before getting into realm of work. Student can apply what had been taught in university and experiences working in industry. The students can also develop their knowledge and skills in this industrial training period. The trainee was introduced to various of things. Students can complete the tasks offered by dedication and enthusiasm. At the conclusion of the industrial training period, the final report provides information about the sector and organization involved in the work performed by the trainee during the industrial training period.